INNOVATIVE DEVELOPMENT OF MESOSYSTEMS IN THE SPHERE OF CHEMICAL TECHNOLOGY (BY THE EXAMPLE OF TATARSTAN REPUBLIC) - C. A. Misbakhova (Russian Journal of Economics and Law, 2017)
Objective: to identify the peculiarities of innovative development of meso-systems basing on the systematization of practical experience of Tatarstan Republic and to conduct the economic-mathematical modeling.Methods: systemic analysis, description and generalization, component and factor analysis.Results: the author substantiates the necessity of development and modernization of petrochemical plants as one of the most important sectors of Russian industry. It is stated that the development of petrochemical wastes’ processing technologies, flexible production technologies, as well as the creation of energy efficient and ecologically safe technologies of oil refining, requires substantial revision of approaches to innovations implementation and financing. The article shows that, despite the large number of high-tech industries, Russia ranks only 20 among developed countries by the level of spending on research and development. The analysis, carried out on the basis of statistical data for the Republic of Tatarstan, showed that the petrochemical complex occupies the leading position in the regional economy, while demonstrating higher efficiency compared to other industries. The main institutions for the petrochemical industry development in the Republic have been defined, including Tekhnopolis "Khimgrad", "Regional center of engineering in the sphere of chemical technologies" JSC and others.To assess the development of the national innovation system, the innovation diffusion factors were studied and systematized. 16 indicators of research and innovation activities in the Republic of Tatarstan for 2010-2014 were selected, which were then grouped into four integrated categories: intellectual activity, research and development, innovation activity of small businesses and innovation outcomes. Factor analysis determined their contribution to the process of the innovations diffusion at the level of 86 %. Scientific novelty: the model of innovation diffusion at the meso-level was substantiated, reflecting the influence of such integral parameters as "Intellectual activity", "R&D", "Innovation activity of small businesses", "Outcomes of intellectual activity", which allows to create balanced chains for creation and commercialization of innovative products at all stages of the scientific and technological results life cycle and their transfer into industry. Practical significance: the main provisions and conclusions of the article can be used in scientific and scientific-educational activities when considering the conceptual issues of innovative development of meso-systems. The materials of the article are of practical importance for the development of models of management of innovation development institutions and in the development strategy of the state innovation policy at the regional level.